1. ## transposition of formula

I've got the following formula

X=k(1-e^(-t/T)

i've managed as part of my assignment to find values for all of the constants or variables except t.

so i now have the formula 10=20(1-e^(-t/0.1)

could anybody show me how to transpose this formula for t ?

2. You bet...

First we need to isolate the term containing the variable.

$10=20(1-e^{-t/.1})$

$\frac{1}{2}=1-e^{-t/.1}$

$-\frac{1}{2}=-e^{-t/.1}$

$\frac{1}{2}=e^{-t/.1}$

taking the natural log of both sides gives.

$ln(1/2)=ln(e^{-t/.1})$

$ln(1)-ln(2)= \frac{-t}{.1}ln(e)$

$-ln(2)=\frac{-t}{.1}$

solving for t gives...

$.1ln(2)=t$

3. Originally Posted by al2308
I've got the following formula

X=k(1-e^(-t/T)

i've managed as part of my assignment to find values for all of the constants or variables except t.

so i now have the formula 10=20(1-e^(-t/0.1)

could anybody show me how to transpose this formula for t ?
$10 = 20 \left ( 1 - e^{-t/0.1} \right )$

$\frac{1}{2} = 1 - e^{-t/0.1}$

$e^{-t/0.1} = \frac{1}{2}$

$-\frac{t}{0.1} = ln \left ( \frac{1}{2} \right ) = - ln(2)$

$t = 0.1 \cdot ln(2)$

-Dan